RISK ASPECTS OF DRUG TAKEN DURING PREGNANCY - Zhuraev, Z.A. (JOURNAL OF EDUCATION AND SCIENTIFIC MEDICINE, 2025)
Currently, 60-80% of pregnant women take medications. More than 5% of all congenital anomalies are caused by drugs. Medicines can threaten the mother, the fetus, or both. In general, the mother is more sensitive to drug poisoning than the fetus. They can have a negative impact on the formation of female and male reproductive cells. Male reproductive cells are damaged less frequently, but alcohol, smoking, caffeine and narcotic analgesics enhance this process. The likelihood of damage to female reproductive cells is much higher, and this can happen long before the development of pregnancy, because a significant amount of time passes between the formation of the egg and fertilization. The need to consider the effect of the drug on the embryo and fetus is obvious, especially after the “tragedy of Thalidomide”.